Magnesia Partially Stabilized Zirconia/Hydroxyapatite Biocomposites: Structural, Morphological and Microhardness Properties - Liliana Bizo; Adriana-Liana Bot; Marieta Mureșan-Pop; Lucian Barbu-Tudoran; Claudia Andreea Cojan; Réka Barabás (Crystals, 2025)
Hydroxyapatite (HAP) is the most widely accepted biomaterial for repairing bone tissue defects, demonstrating excellent biocompatibility and bioactivity that promote new bone formation. Zirconia (ZrO2), known for its strength and fracture toughness, is commonly used to reinforce ceramics. In this study, magnesium oxide (MgO) served as a stabilizer for zirconia, resulting in magnesia partially stabilized zirconia (Mg-PSZ). Both Mg-PSZ and HAP were synthesized via coprecipitation and mixed in specific ratios to create composites through a ceramic method involving mixing, compaction, and sintering at 1100 °C. The samples were characterized using techniques such as X-ray powder diffraction (XRPD), Fourier-transform infrared spectroscopy (FTIR), and scanning electron microscopy/energy-dispersive X-ray spectroscopy (SEM/EDS). Structural analyses confirmed the presence of both monoclinic and tetragonal zirconia phases. Besides, the increased wt.% HAP in the composites produced distinct peaks for hexagonal HAP. Crystallite sizes ranged from 27.45 nm to 31.5 nm, and surface morphology was homogeneous with small pores. Elements such as calcium, phosphorus, magnesium, zirconium, and oxygen were detected in all samples. This research also examined microhardness changes in the materials. The findings revealed enhancement in microhardness for the biocomposite with higher zirconia content, 90Mg-PSZ/10HAP sample, with the smallest average pore size, highlighting its potential for biomedical applications.